Pragmatic Impairment - Perkins, Michael (Cambridge University Press, 2007)
Pragmatics - the way we communicate using more than just language - is particularly problematic for people with speech disorders. Through an extensive analysis of how pragmatics can go wrong, this 2007 book not only provides a clinically useful account of pragmatic impairment, but it also throws light on how pragmatics functions in healthy individuals. Michael Perkins brings mainstream and clinical pragmatics together by showing that not only can our understanding of pragmatics be aided by the study of pragmatic impairment, but that clinical and theoretical pragmatics are better served by treating pragmatic ability and disability within a single framework. It is a comprehensive book aimed primarily at linguists and psycholinguists rather than clinicians, and includes illustrative material on conditions such as autism and aphasia and a wide range of other communication disorders in both children and adults.